IN VITRO RELEASE AND PREDICTED IN VIVO BEHAVIOR OF METRONIDAZOLE VAGINAL FORMULATIONS - MEDINA-LOPEZ, JOSE RAUL; MENDEZ HERNANDEZ, HEDWYN RODOLFO; RUIZ-SEGURA, JUAN CARLOS; HURTADO, MARCELA (International Journal of Applied Pharmaceutics, 2023)
Objective: To document the in vitro release and to predict the in vivo behavior of metronidazole ovules (reference and generic formulations) using USP Apparatus 1 and 4. Prediction of metronidazole plasma concentrations was proposed with the Inverse Release Function approach. The information generated can be considered for the development of new metronidazole vaginal drug products. Methods: Dissolution profiles were obtained using USP Apparatus 1 at 100 rpm and 900 ml of pH 4.5 acetate buffer. Additionally, USP Apparatus 4 at 16 ml/min was used. Drug was quantified at 278 nm every 10 min until 60 min. Mean dissolution time (MDT) and dissolution efficiency (DE) were calculated. Mathematical models such as Korsmeyer-Peppas, Makoid-Banakar, Peppas-Sahlin, Logistic and Weibull were used to fit in vitro data. Percent of prediction error (%PE) for Cmax and AUC0-inf were calculated. Results: Metronidazole ovules of reference formulation released<2% at 60 min in both dissolution methods. Generic formulation released>85%. Values of DE and MDT using USP Apparatus 1 and 4 were 40.40%, 31.94 min, 70.91% and 15.44 min, respectively. In vitro release of generic drug product was better described by Weibull function. %PE for Cmax and AUC0-inf were <15%. Conclusion: Due to limited drug release of reference formulation it was not possible to know the in vitro behavior of this drug product. Generic formulation showed a better in vitro performance by being able to characterize the main dissolution parameters DE and MDT and a release kinetics well defined by a mathematical equation.